Effect of circuit training on body composition, physical fitness, and metabolic syndrome risk factors in obese female college students - Kim, Ji-Woon; Ko, Yeong-Chan; Seo, Tae-Beom; Kim, Young-Pyo (Journal of exercise rehabilitation, 2018)
The purpose of this study was to investigate the effect of a 12-week cir-cuit training program on health-related physical fitness and metabolic syndrome risk factors in obese female college students. Twenty sub-jects with over 30% of accumulated body fat voluntarily participated and were randomly allocated to the control group (n=10) or circuit training group (n=10). The circuit training program consisted of 10 types of resistance and aerobic exercise and was performed 3 times per week for 12 weeks. Health-related physical fitness and metabolic syn-drome risk factors were analyzed to elucidate the effect of the circuit training. Significant differences between groups were determined with two-way repeated analysis of variance and paired t-test. As a result of this study, body weight, % body fat, and body mass index in the circuit training group was significantly decreased compared to the control group. All health-related physical fitness indicators such as back strength, sit-up, sit-and-reach, and 1,600 m running time showed rela-tive effects between groups or over time. Among the metabolic syn-drome risk factors, waist measurement, triglyceride, and total choles-terol were significantly decreased but blood glucose, high-density lipo-protein cholesterol and low-density lipoprotein cholesterol did not show any significant difference. Therefore, the present data suggested that circuit training for 12 weeks may be effective in improving physical fit-ness and preventing metabolic diseases.